Evaluasi Program KOTAKU dalam Penanganan Permukiman Kumuh di Kelurahan Lette - Yulvira Tangketau; Mimi Arifin; Abdul Rachman Rasyid (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2022)
Slum is one of the many problems in cities, including Makassar. So that the government has set the handling of housing and slum settlements as a national target. Therefore, Ditjen Cipta Karya initiated the construction of a collaboration platform between the Regional Government, Provincial Government, Central Government, where the Regional Government is the coordinator to create livable settlements through the Kota Tanpa Kumuh (KOTAKU) program. Lette itself is one of the areas that has received slum settlements for two consecutive years in 2018 and 2019 by KOTAKU. This study aims to assess KOTAKU in handling slums in Lette and KOTAKU's direction in handling slum settlements in Lette. This research uses descriptive analysis method using qualitative and quantitative analysis. This research was conducted from September 2020 to July 2021. The results showed that the KOTAKU Program in handling slum settlements in Lette was quite successful in achieving its goals (quite effective), not successful in the efforts carried out (inefficient) during program implementation, quite successful in the level of benefit/impact (adequacy) in implementation. program, quite successful in public perception (responsiveness) during program implementation and quite successful in accuracy. There are 2 directions to the KOTAKU Program in handling slum settlements in Lette, first, forming a budget plan for handling and solving problems regarding slum settlements that are in accordance with the needs of the local community so that slum settlements are narrower and low income people is reduced and last optimizing working groups so that the community is actively involved in handling.